A Descriptive study on the motivations of college students with depression to participate in a facebook support group - Madamba, Geraldine D.R.; Pinzon, Mary Jannette L. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This qualitative study aims to describe the motivations of college students with depression to participate in a Facebook support group. Specifically, it seeks to address the following 1) to describe the perceived beliefs and intentions of college students with depression joining the online support group on Facebook 2) to describe the motivations of the college students to participate in a Facebook support group and 3) to identify whether needs are gratified by the use of an online support group on Facebook. The current study makes use of a perspective based on the lens of Azjens (1991) Theory of Planned Behavior and Ruggiero's (2000) Uses and Gratifications Theory. While Schramm's (1954) Communication Model comes in as a concept integrating common fields of experience and other relevant literature on communication that relates to the beliefs and intentions as well as the motivations to participate in an online support group on Facebook. Data gathering procedure involved one-on-one in-depth interviews with five college students experiencing depression, aged 18-22 years old. All are members from the online support group, "Philippine Support Group for Anxiety and Depression" on Facebook. All of them were undergraduate college students within Metro Manila. All respondents are diagnosed with depression. Four of them are currently undergoing professional help while one opt to stopped seeking professional help. Four of them are members of more than one online support group on Facebook while the other is only part of one online support group on Facebook. The study found that the respondents had various perceived beliefs and intentions when it came to choosing to participate in the Facebook support group. But one prominent theme would be all five respondents seeking to join an online support group on Facebook in order for them to look for people experiencing the same things they are experiencing. They wanted a sense of a common ground for what they are going through. Social support was evident for all five respondents because they used the online support group on their behalf so that they can be able to get the comfort and sense of commonality they look for especially when triggers or attacks happen. Looking for comfort in a common ground is the top theme that arose from the study since they wanted to feel a sense of belongingness and a sense of being cared for and not being alone in their struggles. In this case, reading about other people's daily motivations or experiences brought them comfort. Each person's experience in participating in an online support group depends on the quality of time they spend on using the online support group on Facebook and whether they are a new member or have been a member for a year or so already. It affects the experience of using the online support group on Facebook because Ruggiero (2000) makes it a point to remind that media usage and habits can differ from person to person and such that between a first-time user of a specific medium and one who is an expert. There are differences when it comes to quantity and quality on the usage of media and in this study the usage of the online support group on Facebook.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.